2001
DOI: 10.1073/pnas.041605498
|View full text |Cite
|
Sign up to set email alerts
|

Delineating developmental and metabolic pathwaysin vivoby expression profiling using the RIKEN set of 18,816 full-length enriched mouse cDNA arrays

Abstract: We have systematically characterized gene expression patterns in 49 adult and embryonic mouse tissues by using cDNA microarrays with 18,816 mouse cDNAs. Cluster analysis defined sets of genes that were expressed ubiquitously or in similar groups of tissues such as digestive organs and muscle. Clustering of expression profiles was observed in embryonic brain, postnatal cerebellum, and adult olfactory bulb, reflecting similarities in neurogenesis and remodeling. Finally, clustering genes coding for known enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
145
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 15 publications
8
145
1
Order By: Relevance
“…go.jp/READ/) (Miki et al 2001;Bono et al 2003). Correlating expression analysis by sequencing subtracted libraries, microarray, and other methods such as SAGE will present further computational challenges.…”
Section: Tissue Cdna Encyclopediamentioning
confidence: 99%
See 1 more Smart Citation
“…go.jp/READ/) (Miki et al 2001;Bono et al 2003). Correlating expression analysis by sequencing subtracted libraries, microarray, and other methods such as SAGE will present further computational challenges.…”
Section: Tissue Cdna Encyclopediamentioning
confidence: 99%
“…A TU is computationally defined to be a group of transcripts that contain a common core of genetic information having the same orientation, which does not necessarily correspond to proteincoding regions . From this collection, 60,770 fully sequenced cDNA clones have been function annotated Okazaki et al 2002) and used for genetics studies, expression profiling (Miki et al 2001), protein-protein interaction studies (Suzuki et al 2003), and alternative splicing (Kochiwa et al 2002). The analysis of polyadenylation signals also suggests that a majority of the 3Ј ends are likely to be true ends.…”
mentioning
confidence: 99%
“…We have constructed such a resource by profiling 46 human and 45 mouse tissues from diverse tissue origins. Whereas several recent studies have also described high-throughput gene expression measurements on diverse tissue sets (7)(8)(9), previous analyses of physiological gene function have been limited to identification of housekeeping genes, and clustering of genes involved in metabolic pathways and development of the central nervous system. The analysis of the data described in the current work has a significantly different and expanded scope.…”
mentioning
confidence: 99%
“…Clustering analysis of gene expression patterns of isolated mouse macrophages and 49 mouse tissues (13,19) demonstrated that macrophage samples clustered independently from these tissues. Macrophages clustered closest to hemopoietic tissues such as the spleen, but were clearly distinct from the rest of the tissues.…”
mentioning
confidence: 99%